Perancangan Sistem Informasi Kawasan Wisata Mandeh Berbasis Web dengan Pendekatan User-Centered Design - Azmi, Luxfy Roya; Ramadhani, Salisa ‘Asyarina; Putri, Vivin Mahat; Azhar, Wafianda (Jurnal Pengembangan Sistem Informasi dan Informatika, 2025)
The Mandeh Tourism Area, located in Pesisir Selatan Regency, West Sumatra, is a leading destination with significant potential in the marine tourism sector. Often referred to as the "Raja Ampat of West Sumatra," this area offers clusters of exotic islands, clear waters, and rich underwater biodiversity that attract both domestic and international tourists. In 2023, the number of tourist visits exceeded two million, reflecting strong interest and the potential for tourism service development. However, the absence of an integrated digital information system remains a barrier to optimizing tourism services. To address this issue, the development of a web-based tourism information system using a User-Centered Design (UCD) approach is proposed as a strategic solution. UCD emphasizes user involvement throughout the design process, from needs analysis to system testing, to enhance information accessibility, user experience, and the competitiveness of the tourism destination. The implementation of this system is expected to support sustainable tourism growth and strengthen the local economy.